APPARATUS HR MANAGEMENT REFORM IN INDONESIA - Vita Nurul Fathya (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Human resources management in government agencies is one of change areas becoming the focus of bureaucracy reform in Indonesia. This article explores plans of change to reform human resources management in Indonesian government agencies. The plans are compared with concepts on effective human resources management. The conclusion is that there is conformity between the government plans under road map on bureaucracy reform and some concepts of human resources management.